Instant XenMobile MDM : a guide to effectively equipping mobile devices with configuration, security, provisioning, and support capabilities using XenMobile, the world's most popular mobile management software /: a guide to effectively equipping mobile devices with configuration, security, provisioning, and support capabilities using XenMobile, the world's most popular mobile management software. (2013) - Unknown
No abstract available